Health risks of obesity (2009)
Obesity is becoming of interest as a non-communicable disease. There is however a dearth of information on obesity in this environment, as literature in developing countries is limited. Review of health risks of obesity is useful in order to increase the pool of available information in Nigeria and to draw attention to obesity and its attendant health risks.